The Millennial Generation - Pasi Pyöriä; Satu Ojala; Tiina Saari; Katri-Maria Järvinen (SAGE Open, 2017)
This article puts to the test the notion that younger generations, most notably the Millennials, value work less than older generations do. The analysis, deploying a linear probability model, is based on Statistics Finland’s Quality of Work Life Surveys, 1984 to 2013. Focusing on labour market entrants aged 15 to 29, we address two main themes: the value given to work, leisure and family life, and work commitment. Regardless of age, the value given to work has remained consistently high for the past three decades. At the same time, leisure and family life have gained increasing importance, not only among the Millennials but also among older generations. The Millennials are more prepared to change to a different occupational field than older employees, but this is not a new tendency, and therefore the generational gap remains unaffected. The evidence does not support the argument that the Millennials are less work-oriented than older generations.